A Novel Cloud Computing Architecture Supporting E-Governance (International Journal of Engineering and Computer Science, 2017)
In this paper Slave Data center and Master Data Center is a technique used to spread a network service workload between two or more devices. Benefits include scalability, reliability, efficiency, redundancy, and minimized response time. The large number of service requests to fulfill the demands of millions of users will broaden the latency problem. Cloud service provider physically may be far away from the clients, compelling data to travel from several mediums and network equipments. So in this paper we are providing the an intelligent & energy efficient Cloud computing architecture is proposed based on distributed datacenters (DDC) which form a client’s instance in nearest neighborhood and fulfill client’s request in optimized latency.